Expert Consensus on Molecular Tumor Boards in Taiwan: Joint Position Paper by the Taiwan Oncology Society and the Taiwan Society of Pathology - Ming-Huang Chen; Wan-Shan Li; Bin-Chi Liao; Chiao-En Wu; Chien-Feng Li; Chia-Hsun Hsieh; Feng-Che Kuan; Huey-En Tzeng; Jen-Fan Hang; Nai-Jung Chiang; Tse-Ching Chen; Tom Wei-Wu Chen; et al. (Journal of Cancer Research and Practice)
Background: The Taiwan Oncology Society (TOS) and the Taiwan Society of Pathology (TSP) have collaborated to present a joint position paper on the molecular tumor boards (MTBs) within the medical institutions of Taiwan. Materials and Methods: To raise awareness of MTBs among health-care professionals, policymakers, and the public, a total of 20 experts from TOS and TSP formulated a joint consensus statement through a voting process. Results: The joint statement proposes key recommendations: (1) MTB discussions encompass diverse molecular analyses including next-generation sequencing (NGS), RNA sequencing, whole-exon sequencing, and whole-genomic sequencing addressing relevant genomic changes, tumor mutation burden, microsatellite instability, and specific biomarkers for certain cancers. (2) MTB meetings should involve multidisciplinary participants who receive regular updates on NGS-related clinical trials. (3) Prioritize discussing cases with unique clinical needs, gene alterations lacking treatments, untreatable neoplasms, or oncogenes unresponsive to targeted therapies. (4) Base MTB discussions on comprehensive patient data, including genetics, pathology, timing of specimen collection, and NGS outcomes. (5) MTBs offer treatment recommendations: standard therapies, off-label use, clinical trials, genetic counseling, and multidisciplinary reviews. (6) MTB effectiveness can be gauged by member composition, case reviews, treatment suggestions, and patient outcomes. Encourage government incentives for MTB engagement. Conclusion: The primary aim of this initiative is to promote the advancement of precision oncology in Taiwan.